Histomorphological studies on the cortex of metanephros in buffalo foetii - SUMAN, MONIKA; BANSAL, NEELAM; UPPAL, VARINDER (The Indian Journal of Animal Sciences, 2011)
The development of metanephros started as metanephric tubules at the age of 4.1 cm CRL (47 days) in the cortex of kidney. The cortex and medulla could be differentiated at the age of 5.7 cm CRL (54 days). Three types of glomeruli, i.e. the subcapsular, intermediate and juxtamedullary glomeruli could be observed in the kidneys of buffalo foetii at 10.3 cm CRL (75 days) onwards. The number of these glomeruli increased with the progression of age of foetus and were found to be more in the right kidney than the left kidney. The proximal and distal convoluted tubules were seen in the cortex of kidney at 5.7 em CRL onwards whereas the collecting ducts were demonstrated in the medullary rays penetrating the cortex of metanephros at 11.2 cm CRL onwards. The formation of different parts of nephron during foetal life may be correlated with the functional activity of metanephros in adult kidney. Â